Probing the origins of magnetism in 2 at% Fe-implanted 4H-SiC. (November 2020) - Zhang, Leifeng; Diallo, Lindor; Fnidiki, Abdeslem; Lechevallier, Luc; Declémy, Alain; Lefebvre, Williams; Juraszek, Jean
Abstract: Here we reported an about 2 at.% Fe-implanted p-type 4H-SiC Diluted Magnetic Semiconductor (DMS). Scanning Transmission Electron Microscopy (STEM) and Atom Probe Tomography (APT) techniques were used to investigate the origins of ferromagnetic behavior. Nanoparticles (1–9 nm) were identified to be Fe3 Si, Fe2 Si, Fe5 Si3, Fe3 Si2, FeSi and FeSi2 phases, the distribution of which is related to Fe distribution. The magnetic properties were studied by Conversion Electron Mössbauer Spectroscopy (CEMS) and Superconducting Quantum Interference Device (SQUID) techniques. The contributions of these Fe-silicides to the ferromagnetism are thus discussed from a quantitative perspective. Graphical abstract: Image, graphical abstract